A geometric approach to factor model identification - Sylvia Kaufmann; Markus Pape (Swiss National Bank, Study Center Gerzensee, 2024)
We use the geometric representation of factor models to represent the factor loading structure by sets corresponding to unit-specific non-zero loadings. We formulate global and local identification conditions based on set conditions. We propose two algorithms to efficiently evaluate Sato (1992)'s counting rule. We demonstrate the efficiency and the performance of the algorithms with a simulation study. An application to exchange rate returns illustrates the approach.
Keywords: C10; C52; C55; E44; F31; 330; Factor model; Global and local identification; Set representation